Autoimmune channelopathies: John Newsom-Davis's work and legacy. A summary of the Newsom-Davis Memorial Lecture 2008. - Vincent, A (2008)
John Newsom-Davis was a key figure in the field of neuroimmunology and combined many outstanding personal qualities with considerable clinical and scientific expertise. His first report of plasma exchange in myasthenia in the late 1970s demonstrated its use both as a treatment and as an experimental tool to establish the pathogenic role of antibodies in neurological disorders. Subsequent investigations into the Lambert Eaton myasthenic syndrome and acquired neuromyotonia showed that these were caused by antibodies to specific ion channels. The field of autoimmune channelopathies is continuing to expand with identification of new antibody-mediated diseases including those affecting the central nervous system. This review will highlight some of his most seminal findings and those that are following on from his work.